Consulta à comunidade : princípios, métodos e avaliação da experiência dos planos diretores do município de Bauru - SP - Rigitano, Maria Helena Carvalho (2008)
This paper presents a collection of consultation methods reported in the technical literature and its applicability. It seeks for identify the most appropriated way to involve the communities in drawing up directors plans and other actions related to the urban planning and management. This because, since the Federal Constitution, 1988, the legislation related to the public policies prescribe the need of popular participation in these programs. It chose to study case the elaboration process of the Participative Director Plan in Bauru - SP, which was evaluated by several segments involved in its process through the application of questionnaires that based on the Likert Scale and according to established principles by Carson and Gelber (2001), with the objective to verifying the reached level of participation in this. In the end, discussions are made about the role of professionals involved in urban planning ahead to the new situation of sharing decisions with the community.